HINTERLAND MEDAN CITY BETWEEN BINJAI CITY: A GRAVITATION APPROACH - Nasir, Muhammad (Jurnal Ekonomi Pembangunan, 2019)
Regional economy explains that there is an urban hierarchical relationship, cities that have higher hierarchy will serve cities that are below it as well as cities that are in hierarchy under supplying cities that are in the hierarchy above them, so there is a gravitational relationship between the two. This study aims to determine the gravitational relationship of Medan city to the hinterland of the city of Binjai. Furthermore, this study also wants to explain its influence on economic growth in both cities. This study uses time series data from 1990-2016, taken from North Sumatera BPS test equipment and analysis tools used are descriptive statistics, gravity models, unit root test, co-integration test, optimal lag, VECM, granger causality test, impulse response function and variance decomposition. The results showed that the city of Medan has a gravity style greater than the gravitational style of the city of Binjai. This is because the city of Medan has a larger area, population, income per capita compared to the city of Binjai. The VECM estimation results show that the gravitational variable in the city of Binjai in lag -1 and lag-2 has a positive and significant effect on the economy of Medan city with a confidence level of 95%. Then the economic variable of the city of Binjai itself in lag-1, the population of the city of Medan in lag-2 and the gravity of the city of Medan in lag-2 had a positive and significant effect on the economy of Binjai city with a confidence level of 95%. While the variable population of Binjai city in lag -1 and residents of the city of Medan in lag -1 negatively affected the economy of Binjai city with a confidence level of 95%.